Government Debt, Government Spending, and Private Sector Behavior - Kormendi, Roger C. (American Economic Review, 1983)
A current-period tax reduction financed by issuing government shifts the timing of tax collection from the current period to the future. If the future taxes implied by government are not fully perceived and discounted by the private sector, there will be a net effect that increases private sector consumption, thus reducing capital accumulation and growth. If, on the other hand, the implied future taxes are perceived and discounted by the private sector, the current-period tax reduction will be used to increase private saving to pay for the future taxes, and government will be absorbed without any real effects on the economy.' The effects of government spending financed by current-period taxation also depend upon private sector perceptions.2 If the benefits of government spending are ignored, private sector consumption will decrease in accordance with the reduction in permanent disposable income. To the extent that government spending is on consumption-type goods that are perceived as substitutes for privately provided consumption goods, there will be a relatively greater reduction in private sector consumption. To the extent that government spending is on investment-type goods yielding future goods and services that are perceived as substitutes for future privately provided consumption goods, there will be a relatively smaller reduction in private sector consumption. The to modeling private sector consumption-saving behavior involves a rather asymmetric set of assumptions as to how the private sector perceives the various elements of government fiscal policy.3 Current-period taxes are assumed to be fully perceived, but current-period government spending is implicitly assumed to be completely ignored by the private sector. In considering permanent personal disposable income, the private sector is assumed to be forward-looking in its assessment of income and taxation. The stock of government is nevertheless included as part of the stock of private wealth, the implicit assumption *Associate Professor of Economics, Graduate School of Business, University of Chicago, 1101 East 58th Street, Chicago, IL 60637. I thank Eugene Fama, Levis Kochin, Michael Mussa, Paul Evans, and an anonymous referee for helpful comments. I am particularly grateful to Daniel Benjamin for contributing many hours of discussion, and Laura Lahaye, who was a research assistant and valuable adviser on earlier drafts. 'The theoretical debate on the burden of the debt has been long standing. Gerald O'Driscoll (1977) documents Ricardo's nineteenth-century position. Robert Barro (1974) reopened the debate by introducing the fundamental issue of intergenerational transfers (also discussed in Merton Miller and Charles Upton, 1974). The empirical side of the debate was initiated by Levis Kochin's (1974) attempt to test for the effects of deficits on consumption and by Martin Feldstein's (1974) attempt to test for the effects of Social Security wealth on consumption. Other empirical contributions include Jess Yawitz and Laurence Meyer (1976), myself (1978) and J. Earnest Tanner (1978, 1979) with respect to the effects of government deficits and debt, and Barro (1978), Michael Darby (1979), and Dean Leimer and Selig Lesnoy (1982) with respect to Social Security wealth. See also interesting recent papers by John Seater (1982), who generates detailed tests of the effects of deficits and on consumption, Charles Plosser (1982), who explores the effects of government spending and shocks on interest rates, and Feldstein (1982), who attempts tests similar to some in this paper (see fn. 29). 2Martin Bailey's (1962, 1971) development of the effects of government spending on private consumption and aggregate economic activity is the seminal contribution. Paul David and John Scadding (1974) extend Bailey's ideas and provide some supporting empirical evidence. More recently, Willem Buiter (1977) and myself (1978) developed models based on Bailey's earlier work. Barro (1981) has an interesting paper on related issues. See also David Aschauer (1982). 3The standard approach incorporates fiscal policy through the concept of personal disposable income and by including the stock of government as part of personal wealth. See, for example, the empirical specification of Albert Ando and Franco Modigliani (1963), which has been the basis of most empirical consumption studies since, and Feldstein (1974) for one of the more influential papers based on the Ando-Modigliani specification.